A stable zinc(II)-organic framework as rapid and multi-responsive luminescent sensor for metal ions in water. Issue 5 (3rd March 2020) - Xu, Xiu-Dian; Liang, Yu; Li, Jun-Feng; Zhou, Lei; Chen, Li-Zhuang; Wang, Fang-Ming
Abstract: A very stable Zn II -organic framework, {[Zn(Titpe)0.5 (bpodc)]·(H2 O)3 }n (1, Titpe = 1, 1, 2, 2-tetrakis(4-(imidazol-1-yl)phenyl)ethane, bpodc = benzophenone-4, 4-dicarboxylic acid), has been synthesized under hydrothermal conditions. Single-crystal X-ray analysis reveals that 1 crystallizes in the monoclinic system and P2 1/c space group. Its overall structure is a 3-D stacking with a porosity of 20.95% and a 4-c type topological network; it shows good stability in many solvents. Studies of the solution-phase detection of metal cations show that Fe 3+ and Cr 3+ ions can quench luminescent emission of 1 . Fluorescence titration experiments show that 1 is more selective to Fe 3+ ( K sv  = 2.8 × 10 4 M −1 ) than Cr 3+ ( K sv  = 1.4 × 10 3 M −1 ). The solution-phase detection for anions by 1 also show high selectivity and sensitivity for Cr2 O7 2– anions ( K sv  = 1.2 × 10 4 M −1 ). With water stability and strong blue luminescence, 1 can potentially apply as a reversible multi-responsive luminescence sensor for Fe 3+, Cr 3+, and Cr2 O7 2– in aqueous solutions. Graphical Abstract: